Digital Image Correlation in the Classroom: Determining Stress Concentration Factors with Webcams. Issue 4 (21st February 2012) - Lava, P.; Coppieters, S.; Van Hecke, R.; Van Houtte, P.; Debruyne, D.
<x xml:space="preserve">Abstract</x> In this study, we introduce graduate students to an experiment with digital image correlation (DIC). From an educational point of view, the aim is to get students familiar with basic aspects of stereovision and DIC, for example, speckle pattern, subset size, focus, aperture, etc. First, a homogeneous uniaxial tensile test is conducted on a rubber dogbone, allowing the determination of the hyperelastic stress–strain relationship. Next, a nondestructive 2D deformation test on a rubber specimen with a specific geometry is performed on a small tensile setup. At various load steps, images are captured with a low‐cost webcam and are processed with our in‐house DIC software which is available for each individual student. Assuming a Mooney–Rivlin material model based on the determined stress–strain data, one can derive stress concentration factors for the specific holes and notches present in the specimen. A comparison is made to analytical calculations of the stress concentration factors and eventually a finite element analysis of the experiment can be performed. In this way, a synergy between experiment, simulation, and theoretical calculations is achieved. Moreover, we have accomplished all stages in the engineering process of determination of material properties, simulation, and validation. The particular experimental setup is chosen to avoid the use of special equipment, for example, sophisticated tensile devices and expensive high‐tech cameras, without losing the focus of the objective.